A indexação em catálogo on-line em bibliotecas universitárias na percepção de usuários integrantes de grupos de pesquisa: uma contribuição ao desenvolvimento de política de indexação na rede de biblioteca da UNESP - Gonçalves, Maria Carolina [UNESP] (2008)
The indexing in online catalogues in the perception of users who are members of research groups becomes crucial in an environment of university libraries so that the catalogue of subject, first restricted to the physical limits of the library and containing only bibliographic records of documents ordered in bookshelves, becomes virtual nowadays. However, users have difficulties when they do their search by subject, because the words they use do not coincide with the terms used by the librarian at the time of indexing. Consequently, the retrieval of information becomes silent and with noise. This issue of the catalogue of subject is often the reflection of a possible deficiency of the work done by librarians, since they do not study about users in order to know their interests and opinions concerning the treatment of the documents content. It is also a reflection of the lack of an indexing policy that guides the steps of indexing. Aiming to contribute to the development of an indexing policy in university libraries under the users’ perspective, the proposal os this research was to do a study of the socio-cognitive context of users who are members of research groups in the areas of Biological and Exact Sciences and Humanities from UNESP, to get a diagnosis of their perception regarding the indexing context. The specific objectives were: developing a study on the indexing process under the indexing policy in institutional environments; investigating a method of a socio-cognitive approach by Verbal Protocol to study the users’ perception; verifying the perception of the user who participates in a research group on indexing information in university libraries for the development of online catalogues. The results showed that the indexing process has some elements of policy, such as completeness, uniqueness and language choice. Both indexing and policy aim to answer the...(Complete abstract, click electronic access below)